From surface structures to the integral depth model of the Kirovograd ore region (Ukrainian Shield). 1 - V. I. Starostenko; V. I. Kazansky; N.I. Popov; G. M. Drogitskaya; V. B. Zayats; O. F. Makivchuk; A. A. Trypolsky; M. V. Chicherov (Геофизический журнал, 2010)
The discovery of a middle-scale mantle trough in the Kirovograd ore district under uranium, gold and lithium deposits brought a new insight into metallogeny of the district and made it necessary to trace its surface structures to the M boundary.In this study, surface structures are described in more detales using numerous data from exploration drilling, relationships between the crustal Kirovograd-Novoukrainsk granitoid massif, mantle-related Korsun-Novomirgorod massif and M interface are discussed, surface and deep structures of uranium ore fields are correlated and vertical metasomatic and ore zonality of large uranium deposits is considered.